Pengaruh Pengendalian Internal Dan Ketaatan Aturan Akuntansi Terhadap Kecenderungan Kecurangan Akuntansi Pada BPKAD Kabupaten Nganjuk - Wanda Febriani; Hero Priono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to determine the effect of internal control and compliance with accounting rules on the tendency of accounting fraud in BPKAD Nganjuk regency. The research method used is quantitative, the type of research data is primary by distributing questionnaires directly to the Nganjuk Regional Financial and Asset Management Agency (BPKAD) office. The population in this research are all employees who work at the BPKAD Nganjuk regency. The method of determining the sample is saturation sampling technique which means all members of the population are determined as a sample. The hypothesis tester uses a multiple linear regression analysis with the help of SPSS 27 to process the data. The result obtained from the research are internal control and compliance with accounting rules give contribution on the tendency of accounting fraud in BPKAD Nganjuk regency. Therefore, if internal control is getting stronger and compliance with accounting rules are increasingly being adhered to in an institute, it can reduce the tendency for accounting fraud at the BPKAD of Nganjuk Regency. Keywords: Internal Control, Compliance With Accounting Rules And Tendency Of Accounting Fraud